DECODING THE VISUAL LANGUAGE: A SEMIOTIC ANALYSIS OF YOUTUBE THUMBNAILS - Iram Sagheer; Ashmal Yasir; Umar Safdar; Shareena, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
YouTube thumbnails are the small, clickable preliminary viewing images that viewers see before clicking on a video. This study examines YouTube thumbnails to identify the common signs and symbols present in these images. It aims to answer questions like what visual elements are frequently used in YouTube thumbnails to draw viewers in and how these elements differ across various types of content. It also discusses the cultural or social meanings these signs and symbols have. In this study, the researchers have explored how various elements, such as colours, images, text, and composition, are strategically employed in YouTube thumbnails to engage viewers. This study uncovers the underlying messages, ideologies, and persuasive techniques embedded in these visual representations by applying semiotic theory. The study used a qualitative approach focussing on thematic analysis to examine sixteen thumbnails collected randomly from different Pakistani YouTube channels. In thematic analysis, we identify and categorise recurring visual elements and symbols in thumbnails to find patterns and meanings. The data is analysed using a method that examines how different forms of communication, like words and pictures, work together. This method was created by Kress and Leeuwen (2006) and helps us understand how these elements work together to convey meaning. Different societal factors were considered, such as religious, cultural, and social, and how these aspects affect the viewer’s overall perception so that the YouTuber might get more views. It has been found that thumbnails with bright colours and big text are more likely to grab the user's interest. This helps us understand which design features work best for getting more viewers and making content more noticeable. It helps us understand the purpose of thumbnails, which can make them more effective at attracting viewers. This research is highly beneficial for YouTubers who want to construct professional thumbnails because it may seduce a large audience. This study shows what's popular in YouTube thumbnails and which type of content grabs viewers’ attention. Knowing these trends can help content creators make better thumbnails as trend changers.